As a Biomarker: Comparing the level of IL-35 in Biological Fluids with Age and Sex in Periodontitis Patients - Al-Kaabi, Siham Jasim; Habeeb, Suhair Abdulkareem; Mohsin, Azhaar Jasim (Journal of Science in Medicine and Life, 2024)
Background: The Periodontitis is one of the most common diseases that affect dental health. It also poses a threat to human life when associated with other diseases, and since interleukin-35 is a newly type of cytokines belong to interleukin-12 family which is suggested to contribute together with some cytokines to the process of inflammation, so this study was designed to investigate the importance of interleukin-35 and evaluate its levels in gingival crevicular (GCF), saliva and serum of periodontitis patients compared to sex and age, in order to revealing the possibility of its future use as a biomarker and diagnostic tool for the disease. Materials and Methods : 60 participants, 40 periodontitis patient and 20 healthy person for control, by using Enzyme-linked immunosorbent assay (ELISA) kits were measured the levels concentration of interleukin 35. Results: The results obtained that there are significant differences between GCF and saliva concentration of IL-35 ( 147.3, 50.84 )pg/ml in patients compare with healthy group (79.54, 18.99) pg/ml respectively, also there are no significant between female and male of IL-35 levels, When comparing the levels of interleukin 35 according to age groups, it was found that there was an increment in its levels in the serum among the elderly within the age group (55-65)years. Conclusion: The IL-35 appears to play a part in periodontal disease pathogenesis and it is possible to conclude that the IL-35 concentration may be considered as diagnostic biomarker in GCF or saliva for chronic periodontitis.